Activity in the Medial Temporal Lobe Predicts Memory Strength, Whereas Activity in the Prefrontal Cortex Predicts Recollection - Kirwan, C. Brock (Society for Neuroscience, 2008)
Functional magnetic resonance imaging studies of recognition memory have often been interpreted to mean that the hippocampus supports recollection and that the adjacent perirhinal cortex supports familiarity. Other work points out that these studies have confounded recollection and familiarity with strong and weak memories. In a source memory study, we used two novel approaches to data analysis that allowed item memory strength and source memory strength to be assessed independently. First, we identified regions in both hippocampus and perirhinal cortex in which activity varied as a function of subsequent item memory strength while source memory strength was held constant at chance levels. Second, we identified regions in prefrontal cortex in which activity varied as a function of subsequent source memory strength while item memory strength was held constant. These findings suggest that activity in the medial temporal lobe is predictive of subsequent memory strength, whereas activity in prefrontal cortex is predictive of subsequent recollection.